Clinical characteristics and risk factors associated with severe disease and outcome of patients with COVID-19 - KORTEN, VOLKAN (My University, 2022)
Introduction: Since the beginning of the pandemic, factors associated with mortality in patients with corona virus infection disease 2019 (COVID-19) have been investigated. Comorbidities and increased age have been frequently reported to be associated with mortality. We aimed to evaluate the factors associated with unfavorable outcome of patients with COVID-19 at an early period of the pandemic. Methodology: This single center, retrospective, observational study was conducted among laboratory confirmed COVID-19 patients hospitalized between March 11 and May 5, 2020, at Umraniye Training and Research Hospital, Istanbul, Turkey. The effects of the severity of illness, comorbidities, symptoms, and laboratory findings on the clinical outcome were evaluated. Factors associated with unfavorable outcome (necessity of mechanical ventilation or death) were examined using Cox proportional hazards models. Results: Out of a total of 728 patients, 53.8% were men and median age 54 years. The 30-day mortality rate was 4.9% among all hospitalized patients. A logistic regression model identified six predictors of unfavorable clinical outcome: age, severity of illness, the numbers of comorbidities, lymphopenia, high levels of C-reactive protein, and procalcitonin. Conclusions: The mortality rate was lower among the patients with COVID-19, hospitalized during the early period of the pandemic. Older age, higher severity score on admission, the numbers of comorbidities, higher levels of C-reactive protein, procalcitonin, and lymphopenia were identified to be associated with unfavorable outcome of the hospitalized patients with COVID-19.
Keywords: Yaşam Bilimleri; Temel Bilimler; Life Sciences; Natural Sciences; BULAŞICI HASTALIKLAR; İmmünoloji; Yaşam Bilimleri (LIFE); INFECTIOUS DISEASES; IMMUNOLOGY; Life Sciences (LIFE); Genel İmmünoloji ve Mikrobiyoloji; Bulaşıcı hastalıklar; Sağlık Bilimleri; General Immunology and Microbiology; Immunology; Infectious Diseases; Health Sciences; COVID-19; Mortality; Outcome; PREDICTORS; INFECTION